Encyclopedic reference of cancer - Schwab, Manfred (Springer-Verlag, 2001)
This comprehensive encyclopedic reference provides rapid access to focused information on topics of cancer research for clinicians, research scientists and advanced students. With an A-Z format of about 2000 entries, over 220 contributing authors provide a complete reference to cancer. The merging of different basic and clinical scientific disciplines towards the common goal of fighting cancer makes such a comprehensive reference source all the more necessary, providing definitions of common acronyms and short definitions of related terms and processes in the form of keyword entries. In addition to the keyword entries, there are detailed entries termed essays, which provide comprehensive information on syndromes, genes and molecules, and processes and methods. Each essay is well-structured, with extensive cross-referencing between all entries. The book is accompanied by a CD-ROM, which contains the full text and facilitates searches.
Includes bibliographical references
Keywords: Wörterbuch; CD-ROM; Krebs